Student Evaluation of Teaching: More Harm than Good? - M. O. Abramova; A. V. Filkina (Высшее образование в России, 2023)
Student evaluation of teaching (SET) has more than forty years of history as a tool of feedback in North American, Australian and European universities. In Russian universities it is not widespread, although increasing its implementation could solve the problem of Russian students feeling that they are not involved in the management of the educational process and improve the quality of courses and teaching. The barriers to the implementation of SET in the Russian higher education system, among other things, are concerns and prejudices of teachers and students, who see SET more as a problem than an effective tool. In this article, authors analyze the most common faculty concerns about student evaluations of teaching, obtained from ten focus groups in five Russian universities. Authors put collected opinions in the context of the recent methodological discussions about the validity of Student Evaluations of Teaching. The main idea is that SET is an effective tool of getting feedback in higher education and involvement of students and teachers in a dialogue and cooperation in the educational process, but highly questionable as a data source for administrative decisions.